13 Men who perpetrate physical and technology-delivered intimate partner violence: correlates with substance use and beliefs about children. (9th June 2015) - Singh, Vijay; Lee, Shawna; Epstein-Ngo, Quyen; Carter, Patrick; Cunningham, Rebecca; Walsh, Tova; Tolman, Richard
Abstract : Statement of purpose: Few studies assess men who perpetrate intimate partner violence (IPV) and no studies have addressed male technology-delivered aggression (TDA), or their correlates. The purpose of this study is to determine the prevalence and correlates of male physical IPV perpetration and TDA. Methods/approach: A national sample of U.S. men (18–35 y/o) received survey with validated measures examining physical IPV perpetration, TDA (insulted partner, sent threatening messages, asked partner where they were at, checked partner's phone without permission, accessed partner's account without permission), demographics, depression, alcohol and substance use, and belief that children are harmed by parental IPV. Results: Prevalence of physical IPV perpetration was 19.5% (n = 183), and TDA was 29.8% (n = 289) among this national sample of males with partners (n = 1064; mean age 26.5; 57.5% white). Multivariate analyses identified alcohol (AOR 1.08, 95% CI 1.03–1.13), illicit drugs (AOR 1.56, 95% CI 1.19–2.04), and non-medical prescription pain medication (AOR 1.81, 95% CI 1.31–2.51) as associated with increased risk of physical IPV perpetration, while belief that children are harmed by parental IPV (AOR 0.67, 95% CI 0.50–0.90) was associated with decreased risk of physical IPV perpetration. Alcohol (AOR 1.07, 95% CI 1.03–1.12) and non-medical prescription pain medication (AOR 1.56, 95% CI 1.13–2.16) were associated with increased risk of TDA. Conclusions: In the U.S., nearly 1 out of 5 men reports physical IPV perpetration, and nearly 3 out of 10 men report perpetrating TDA. Male physical IPV perpetration and TDA correlates are similar. Significance/contributions: No prior studies have examined the combined prevalence of male perpetration of IPV and TDA among a national sample. This study provides data to inform prevention efforts for male perpetration of IPV and TDA. Interventions should include focus on substance use including non-medical prescription pain medication, and beliefs about effects of parental IPV on children.